Comparison of Great Saphenous Vein Occlusion and Venous Clinical Severity Score in Chronic Venous Insufficiency (CVI) Patients Using and Not Using Compression Stockings after Endovenous Microwave Ablation (EVMA) - Muhammad Bob Muharly Rambe; Dedy Pratama; Dewi Sumaryani Soemarko (Eduvest - Journal of Universal Studies, 2026)
Endovenous Microwave Ablation (EVMA) is a minimally invasive thermal technique for treating venous insufficiency, known for its low complication rates and fast recovery. While compression stockings are commonly recommended after other thermal ablation procedures such as EVLA and RFA, their effectiveness following EVMA remains unclear and lacks standardized guidelines. This study aimed to compare great saphenous vein (GSV) occlusion success and changes in Venous Clinical Severity Score (VCSS) between patients who used compression stockings and those who did not after EVMA. This prospective cohort study included patients with chronic venous insufficiency (CVI) who underwent EVMA at Cipto Mangunkusumo Hospital between September and November 2025. Data analysis was conducted using Fisher’s exact test and the Mann–Whitney test. The results showed that all 40 patients achieved 100% GSV occlusion one week after EVMA, with no significant difference between the two groups (p=1.00). Preoperative VCSS scores were also comparable between the no-stocking group (10.40 ± 1.85) and the stocking group (11.25 ± 2.88) (p=0.274). Postoperatively, both groups experienced a decrease in VCSS scores; however, the reduction was significantly greater in the stocking group (median 6 vs. 8; p=0.015). The median decrease in VCSS was also higher in the stocking group (4 [2–10]) compared to the no-stocking group (2.50 [0–7]; p=0.012). Component analysis revealed that compression stockings significantly improved only the pain parameter (p=0.004). In conclusion, compression stockings do not affect GSV occlusion rates after EVMA but provide better clinical improvement, particularly in reducing postoperative pain.